Konsekuensi dari Influencer Endorsement - Muhammad Rizky Ananda; Dhafa Zulfikar Alfarissy Mawardi; Fatik Rahayu (Departement of Mathematics Education, 2023)
The purpose of this study is to obtain related empirical evidence: To analyze the positive influence of Influencer Endorsement and Brand Trust on Repurchase Intention. The sampling technique in this study used